Al-Nour Al-Yaqzaniah Newspaper and Reform Issues in Algeria (1931-1933) - khelil, Kamal (The Algerian Historical Journal, 2026)
This research paper examines and analyzes one of Sheikh Ibrahim Abi Al-Yaqzan's most important newspapers, "An-Noor" (1931-1933). This newspaper has not received the same level of scholarly attention as other newspapers such as "Al-Ummah". Over the course of its two-year lifespan and 78 issues, "An-Noor" carried within its pages a wealth of commendable positions that characterized Sheikh Abi Al-Yaqzan's journalism. These positions included defending the national identity, true Islam, and the unity of the Algerian people. The newspaper also continued the mission of the Association of Algerian Oulema Muslim south by publishing all of its meetings, ideas, and reports.